Development Of An Expert System To Identify Implementation Gaps Of Ohsas 18001 In Manufacturing Industries - Suri, Akash (2007)

(untitled)
An expert system (ES) has been developed to perform OHSAS 18001 Gap Analysis for the small and medium scale manufacturing industries in Malaysia. OHSAS 18001 is the standard for occupational safety and health management system. The expert system was written using JavaScript version 1.4 and is named Gap Analysis Expert System (GAES). Although OHSAS 18001 is a proven safety management system, the major problem among small and medium scale manufacturing companies is its implementation, mainly due to cost factors. This fact has been derived after the researcher received direct feedback from manufacturing companies during audits. The approach in the development of the system starts with surveys. Two categories of survey are done, that is the domain expert interviews and the field surveys. Two domain experts are interviewed and the questionnaires for the field survey are firmed up. The field survey covers 30 OSH consultants who comment on 30 different factors that would exert an influence on the implementation of OHSAS 18001. The raw data obtained in the field surveys is processed and a ranking of factors is subsequently derived. The field surveys reveal that the three most important factors that exert an influence in the implementation of OHSAS 18001 are Safety Culture, Process Hazard Analysis and Job Training. Indeed the top ten factors from the survey are given close attention and they are matched against the sixteen statements found in the GAES. The sixteen statements contained in the GAES originate directly from the clauses of OHSAS 18001 standard. This exercise would indicate the statements in the GAES that would need to be considered very carefully when administering the expert system, thus enhancing accuracy and reliability. The GAES has been found to be a user friendly expert system that churns out the final safety gap of an organization expressed in percentage value. This finding is expected to initiate and spearhead efforts in the implementation of OHSAS 18001 among small and medium scale manufacturing companies. Finally, the GAES was field tested in two organizations, IBI Brass (M) Sdn Bhd and Topaz Evergreen (M) Sdn Bhd.